2022
DOI: 10.1136/bmjgh-2021-007735
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic risk markers of arthropod-borne virus (arbovirus) infections: a systematic literature review and meta-analysis

Abstract: IntroductionArthropod-borne viruses (arboviruses) are of notable public health importance worldwide, owing to their potential to cause explosive outbreaks and induce debilitating and potentially life-threatening disease manifestations. This systematic review and meta-analysis aims to assess the relationship between markers of socioeconomic position (SEP) and infection due to arboviruses with mosquito vectors.MethodsWe conducted a systematic search on PubMed, Embase, and LILACS databases to identify studies pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 71 publications
3
18
0
Order By: Relevance
“…Our study found markers of social vulnerability, such as living in the Northeast, the mother’s race/ethnicity, years of education and marital status, to be associated with a higher risk of CZS. The findings are broadly consistent with a 2022 systematic review of socioeconomic risk factors for arbovirus infections that found an association between lower education, income poverty, low healthcare coverage, poor housing materials, interrupted water supply, non-white ethnicities and migration status and arbovirus infection 14. Indicators of low socioeconomic position associated with increased CZS risks may be explained, in part, by increased exposure to infected mosquitoes during pregnancy due to community-level environmental factors such as interrupted water supplies/sanitation and inadequate housing conditions.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our study found markers of social vulnerability, such as living in the Northeast, the mother’s race/ethnicity, years of education and marital status, to be associated with a higher risk of CZS. The findings are broadly consistent with a 2022 systematic review of socioeconomic risk factors for arbovirus infections that found an association between lower education, income poverty, low healthcare coverage, poor housing materials, interrupted water supply, non-white ethnicities and migration status and arbovirus infection 14. Indicators of low socioeconomic position associated with increased CZS risks may be explained, in part, by increased exposure to infected mosquitoes during pregnancy due to community-level environmental factors such as interrupted water supplies/sanitation and inadequate housing conditions.…”
Section: Discussionsupporting
confidence: 87%
“…The findings are broadly consistent with a 2022 systematic review of socioeconomic risk factors for arbovirus infections that found an association between lower education, income poverty, low healthcare coverage, poor housing materials, interrupted water supply, non-white ethnicities and migration status and arbovirus infection. 14 Indicators of low socioeconomic position associated with increased CZS risks may be explained, in part, by increased exposure to infected mosquitoes during pregnancy due to community-level environmental factors such as interrupted water supplies/sanitation and inadequate housing conditions. A literature review on infectious diseases in Brazil published in 2011, 29 had already stressed the failure of the control of Aedes aegypti in the country, which at that time was responsible for major dengue epidemics in the country and is the main vector of ZIKV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The weighted seroprevalence of dengue, zika and chikungunya was higher in areas classified as low and intermediate socioeconomic levels when compared to the high socioeconomic strata which have greater coverage of sanitation, regular water supply and where most of the population live in apartment buildings. In general, our data also reinforce the role of unplanned urbanization and poverty as one of the factors that influence the incidence and expansion of arboviruses [63, 64].…”
Section: Discussionsupporting
confidence: 82%
“…Especially on the webpages we sampled, it was not rare for messaging to give the impression that spillover risk is entirely dependent on land change. This could divert attention from other factors that may increase zoonotic disease spillover risk, such as the wildlife trade (Karesh et al 2005 ), wildlife farming (Magouras et al 2020 and the references therein), global travel (Baker et al 2022 ), climate change (Carlson et al 2022 ), socioeconomics (Power et al 2022 ), and transmission to researchers working on ­zoonotic diseases (National Research Council 2012 ).…”
Section: Implications Of Simplistic Messagingmentioning
confidence: 99%